What to expect the toddler years - Eisenberg, Arlene. frey50; Murkoff, Heidi Eisenberg; Hathaway, Sandee Eisenberg (New York : Workman Pub., 1994)
Covering years two and three of a child's life, this comprehensive guide for parents of toddlers contains useful information about sleeping problems, discipline, peer pressure, toilet training, and other topics.
Getting your toddler talking -- Play is the toddler's work -- Accentuating the senses -- How to encourage learning, thinking, and new experience -- All about TV and toddlers -- Kindness toward animals -- Dealing with toddler fears and phobias -- Traveling with your toddler -- Building self-esteem -- Encouraging creativity and imagination -- Some chronic health problems -- Common toddler illnesses -- Moments to remember.
Includes index.
Keywords: Toddlers; Child rearing; Child Development; Child Rearing